Radio Frequency Identification: an enabler of agile supply chain decision-making. (19th November 2007) - Butcher, Tim
Agile supply chains are dependent upon timely, accurate and precise information. Radio Frequency Identification (RFID) technologies can provide real-time automated data collection from across the supply chain to improve decision-making. Hence, RFID has the potential to deliver even greater levels of agility. This paper discusses two RFID implementation case studies to evaluate the impact of RFID on supply chain decisions. It is found that RFID-enabled decision-making is reliant on cooperative working across the supply chain, and upon the competences of the decision-makers. Supply chains will be redesigned for RFID implementation, and must address its socio-technical impact for the technology to deliver its predicted benefits.